Expressing Added Value in Food Supply Chains - Zidar, Nejc; Turk, Jernej; Prišenk, Jernej (Agricultura Scientia, 2023)
Value-added food supply chains are chains that maintain positive social, environmental, and community values which are integrated into the production process from the primary producer to the final consumer, ensuring economic, social, and environmental sustainability, thus forming a sustainable agricultural and food production system. The evaluation of the value added in each chain is based on indicators, which are a tool to measure changes in the actual situation or to show performance trends in achieving the progress set by the objectives. The presented indicators are based on publicly available statistics and foreign literature that allow measuring value added in specific livestock chains at aggregate level (beef production, pork production and dairy production) and are based on publicly available statistics in the Republic of Slovenia. The need to produce indicators of value added in livestock food supply chains arises from the large differences in structural changes in the sector itself and in the development and economic performance of the various livestock industries.
Keywords: food supply chain; value-added; indicators; sustainability; economic, social and environmental aspect